Islamic Art and Architecture: A Reflection of the Culture and Tradition of Islam - Stella Eme Osim (SOCIETIES: Journal of Social Sciences and Humanities, 2021)
The culture of each society and religion is identified through its manifestations such as language, art, and architecture. Art and architecture as a matter of human life reflect the culture or tradition in every society interacting closely with structural, historical, political, economic, and social features of that society. Islam, therefore, has its style of art and architecture that draws something creative that reflects its thought and practice. It also serves as a channel for communication that makes Islam share its religious ideas and thoughts with other people. In this paper, therefore, the writer looks at Islamic art and architecture. In doing so, the researcher explains what Islamic art and architecture are all about and states some kinds of arts and architectural work in Islam with pictures shown on the appendix page of this paper. The history of Islamic art is also considered in this study. The basic issues the study discovers among others are that Islamic art is not of a specific religion, time, place, or of a single medium. Islamic religious art differs from Christian religious art as it sees the depiction of the human form as idolatry, and thereby a sin against Allah, forbidden in the Qur'an. The writer concludes that art and architecture are forms of preserving the culture and tradition of a community and a religion. It reflects society or a religious belief, cultural values, and so on. Art and architecture are used to share religious ideas and thoughts with other people, hence their relevance in making one have more understanding about Islam. The study uses a qualitative method of research where secondary sources from books, journals and the internet are accessed and used in the work.